2010
DOI: 10.1111/j.1755-5949.2010.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides and Their CNS Targets

Abstract: Ginsenosides are a special group of triterpenoid saponins attributed to medical effects of ginseng. Therefore, they have been research targets over the last three decades to explain ginseng actions and a wealth of literature has been presented reporting on ginsenosides' effects on the human body. Recently, there is increasing evidence on beneficial effects of ginsenosides to the central nervous system (CNS). Using a wide range of in vitro and in vivo models, researchers have attributed these effects to specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 96 publications
(119 reference statements)
0
49
0
2
Order By: Relevance
“…The ginseng saponin metabolite, compound K, is absorbed from the gastrointestinal tract to the blood (Akao et al, 1998). Compound K has a variety of pharmacological activities, including antitumor, antidiabetic, antiallergic, and anti-inflammatory effects (Jia et al, 2009;Radad et al, 2011). Our group has reported that compound K suppresses glioma invasion via the inhibition of MMP-9 expression (Jung et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The ginseng saponin metabolite, compound K, is absorbed from the gastrointestinal tract to the blood (Akao et al, 1998). Compound K has a variety of pharmacological activities, including antitumor, antidiabetic, antiallergic, and anti-inflammatory effects (Jia et al, 2009;Radad et al, 2011). Our group has reported that compound K suppresses glioma invasion via the inhibition of MMP-9 expression (Jung et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1), is a metabolite of the protopanaxadiol-family ginsenoside produced by intestinal bacteria after orally taking ginseng extracts. CK possesses several pharmacological activities including antitumor, anti-inflammatory and anti-allergic action (Helliwell et al, 2015;Radad et al, 2011). Our previous studies demonstrated that CK played their anti-inflammatory and immunoregulatory effect in collagen-induced arthritis (CIA) and adjuvant arthritis (AA) by inhibiting abnormal T cells activation and differentiation (Chen et al, , 2015Wu et al, 2014;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…investigated against an array of neurological disorders and for their ability to increase cognitive enhancement in various cellular and animal models; examples include B. monnieri (a cognitive enhancer, used against dementia, epilepsy), C. asiatica (reported against cognitive impairment) (Kumar et al, 2011), G. biloba (reported for activity in focal cerebral ischemia and as an anti-amnestic) (Abd-Elhady et al, 2013; Yin et al, 2014), P. ginseng (neuroactive) (Kuo et al, 2003), W. somnifera (used as a CNS active agent and against neurodegenerative disorders) (Ven Murthy et al, 2010), curcumin (reported for activity against ischaemia/hypoxia, neuroinflammation and dementia) (Esatbeyoglu et al, 2012), fisetin (neurotrophic effects)(Maher, 2006), ginsenosides (CNS active)(Radad et al, 2011), naringin (reported against memory impairment)(Prakash et al, 2013), quercetin (tested against brain ischemia), Sallylcysteine (reported against stress-induced neuronal death)(Imai et al, 2014) etc.These findings indicate a possible common mechanism of neuroprotection provided by these plants and their derived compounds. The anti-HD properties of certain extracts also indicates the possible synergy between…”
mentioning
confidence: 97%